Accountability of Land Deed Officials (PPAT) for Making Covernotes in Banking Credit Agreements - Purnomo, Sigid (TABELLIUS: Journal of Law, 2024)
This study aims to examine and analyze the right time for Notaries-PPATs to issue covernotes, as well as the urgency and legal problems with the issuance of covernotes, along with the responsibilities of Notaries-PPATs in issuing covernotes. This study uses a normative juridical method with a literature study data collection or processing technique. The research specification is analytical prescriptive, namely a study aimed at obtaining suggestions on what should be done to overcome certain problems that can produce new arguments, theories or concepts as prescriptions in solving the problems faced. The results of this study indicate that the right time for PPATs to issue covernotes is when PPATs have truly had confidence in everything that is agreed upon in the covernote. The urgency of issuing a covernote for creditors as a temporary legal umbrella before the things agreed in the covernote are fulfilled. Problems that arise from within the PPAT include the lack of caution and indecisiveness of the PPAT in checking the certificate. All legal consequences related to the covernote are the full responsibility of the PPAT concerned. Notaries-PPATs are required to be based on the principle of caution. That before issuing a covernote, they must first check the collateral object, so that it can be ensured that the certificate is clean. Notaries-PPATs are responsible for the promises contained in the covernote. Banks should be selective in choosing debtors and Notaries-PPATs as partners.